Ibridismo come forma d’essere nella poetica di Derek Walcott - Landucci, Valentina (TransCulturale, 2022)
The article proposes the aesthetic dimension according to the poetics of D. Walcott as a viaticum to corroborate the edifying power of cultural hybridisation processes enacted during the construction of identity; such dimension is the elected place in which the imaginary support of educational practice is revived. The proposed itinerary will unfold through the reflections of É. Glissant, M. de Certeau and H. K. Bhabha in order to provide tools to face the complexity of reality, to strengthen the poetics of relation capable of exalting heterogeneity, to escape the levelling inclusion which operates in the precept of the transparency of the other, respecting the opacity necessary to preserve its mystery.